Streptococcal tonsillitis as a cause of urticaria Tonsillitis and urticaria - Calado, G (2011)
BACKGROUND: The primary role of infections in chronic urticaria (CU) is controversial. We hypothesised that streptococcal tonsillitis (ST) could be a primary cause of CU or acute recurrent urticaria (ARU). METHODS: Retrospective study of 14 outpatients observed between January 2000 and December 2009, with CU/ARU and clinical and/or laboratorial suspicion of an aetiopathogenic link with ST. Clinical history, objective examination and laboratorial study were looked for. Three groups were defined: spontaneous resolution of urticaria, resolution after tonsillectomy, and still symptomatic. RESULTS: In these patients, a causal relationship between ST and urticaria is supported by: markers of streptococcal infection, the perception of a clinical relationship between tonsillitis and urticaria, the decrease of urticaria severity with early antibiotherapy to tonsillitis and urticaria resolution after tonsillectomy. CONCLUSIONS: Our study encourages the investigation of tonsillitis in these otherwise idiopathic patients, especially until young adulthood and even in the absence of any symptoms.